ANALISIS DAN PENGEMBANGAN KAWASAN WISATA KAWAH PUTIH KECAMATAN SILAU KAHEAN, KABUPATEN SIMALUNGUN, PROVINSI SUMATERA UTARA - Polman Roni Tua S; Siti Latifah; Pindi Patana (Peronema Forestry Science Journal, 2016)
Kawah Putih Dolok Tinggi Raja is a target destination of tourist attraction in Simalungun. One of the benefits that can be gained is the development of natural forest areas for ecotourism. This study aims to (1) analyzing the potential attraction to Kawah Putih for the development of ecotourism. (2) to analyze the problems of nature tourism development strategy in the region SWOT attractions. This researched used Analysis SWOT. The result showed that the Attraction Nature Kawah Putih  has decent potential to be developed on the level 72,91%, and the feasibilty of the SWOT of analysis are quadran I, which means to have strength and opportunities can develop a tourist attraction. Keyword : development, Kawah Putih, potential attractions, Simalungun District